Electrically-detachable two-component polyurethane adhesive with excellent adhesive property as well as preparation method and application of electrically-detachable two-component polyurethane adhesive
By using the oxide -based solid -state electrolyte and/or sulfide base solid electrolytes in dual -group polyurethane adhesives, combined with sirriomide coupling agent, the existing electrical disassembly adhesives are The gap achieves high -performance, electrical disassembly adhesive effects.
Patent Information
- Application Number
- CN202411459633.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-24
AI Technical Summary
The existing electrically disassembled two-component polyurethane adhesives have a large gap with traditional two-component polyurethane adhesives in terms of bonding strength and reliability, and it is difficult to meet the market's high-performance, electrically disassembled adhesives. agent demand.
By using the oxide -based solid -state electrolyte in dual group polyurethane adhesives and/or sulfide base solid electrolytes, combined with sirriiner coupling agent, prepare A and B components, each independent preservation and cooperate with each other under power control conditions. Practice to achieve the effect of excellent adhesion and disassembly.
The high -adhesive strength and good demolition of polyurethane adhesives in dual groups are realized, and the needs of the market for high -performance, electricity disassembly adhesives, and have broad practical prospects.
Smart Images

Figure BDA0005091502180000151 
Figure BDA0005091502180000161
Abstract
Description
Technical Field
[0001] The invention belongs to the field of two-component polyurethane adhesives, and specifically relates to a two-component polyurethane adhesive with excellent bonding performance and electrical disassembly, and a preparation method and application thereof. Background Art
[0002] Two-component polyurethane adhesives are an important category among the many types of polyurethane adhesives. Due to the advantages of low construction temperature, high bonding strength, wide applicable substrates, and good reliability, two-component adhesives are widely used in many fields such as automobiles, construction, new energy batteries, and consumer electronics. Two-component polyurethane adhesives are usually composed of two components, A and B. The two components are packaged separately and can be mixed in a certain proportion before use to achieve the effect of curing and bonding. The two components A and B of the two-component polyurethane adhesive can be divided into a main agent and a curing agent. Usually, the main body of one component is a polyol-terminated composition, and the main body of the other component is a polyisocyanate-terminated composition. After the two components A and B in the two-component polyurethane adhesive are mixed, the polyol and the polyisocyanate can undergo nucleophilic addition reaction and cure. After curing, the two-component polyurethane adhesive can form a high bonding strength and has excellent reliability. However, due to the high bonding strength of the two-component polyurethane adhesive, once poor assembly occurs or abnormal parts need to be replaced, the process of disassembling the cured adhesive often requires a lot of cost. Therefore, there is an urgent need in the market for a two-component polyurethane adhesive that reduces the difficulty of disassembly to meet the widespread demand for adhesive removal.
[0003] In recent years, there is a technology that adds a liquid electrolyte material composed of an alkali metal salt and a solvated matrix to a two-component polyurethane adhesive to give the two-component polyurethane adhesive the function of being disassembled under power-on conditions, but this also makes the two-component polyurethane adhesive have the defects of low bonding strength and poor reliability. Since the existing electrically disassembled two-component polyurethane adhesives still have a large gap in bonding strength and reliability compared with the currently widely used traditional two-component polyurethane adhesives, it is urgent to develop a two-component polyurethane adhesive that can be disassembled under power-on conditions and has excellent bonding properties to meet the market demand for high-performance, electrically disassembled two-component urethane adhesives in actual application scenarios. Summary of the invention
[0004] The purpose of the present invention is to provide a two-component polyurethane adhesive with excellent bonding performance and electrical disassembly, as well as a preparation method and application thereof, in order to address the problem that the existing electrically disassemblyable two-component polyurethane adhesive has a large gap in bonding strength and reliability compared with traditional two-component polyurethane adhesives.
[0005] In a first aspect, the present invention provides a two-component polyurethane adhesive, comprising independently stored component A and component B; the weight ratio of the component A to the component B is (1-2):1; the component A contains a first polyol compound, a small molecule chain extender, a first solid electrolyte, a first silane coupling agent, and optionally a first filler, a catalyst, and a first water absorbent; the mass ratio of the first polyol compound, the first solid electrolyte, and the first silane coupling agent is 100:(5-37.5):(5-25); the component B contains an isocyanate-terminated polyurethane prepolymer, a second solid electrolyte, a second silane coupling agent, and optionally a second water absorbent and a second filler; the mass ratio of the isocyanate-terminated polyurethane prepolymer, the second solid electrolyte, and the second silane coupling agent is 100:(5-45):(5-40); the first solid electrolyte and the second solid electrolyte are each independently an oxide-based solid electrolyte and / or a sulfide-based solid electrolyte.
[0006] In a second aspect, the present invention provides a method for preparing the above-mentioned two-component polyurethane adhesive, the method comprising: mixing a first polyol compound, a small molecule chain extender, a first solid electrolyte, a first silane coupling agent, and an optional first filler, a catalyst, and a first water absorbent to obtain a component A; mixing an isocyanate-terminated polyurethane prepolymer, a second solid electrolyte, a second silane coupling agent, and an optional second water absorbent, and a second filler to obtain a component B, and the components A and B are stored independently.
[0007] In a third aspect, the present invention also provides the use of the above two-component polyurethane adhesive in bonding electronic products.
[0008] In existing two-component polyurethane adhesives, the detachable performance is usually achieved by adding liquid electrolyte materials. However, although the use of liquid electrolyte can give the two-component polyurethane adhesive the performance of detachable when powered on, it will seriously affect the bonding strength of the two-component polyurethane adhesive. In this regard, after in-depth research, the inventors of the present invention found that one of the main reasons for the significant decrease in the bonding strength of the two-component polyurethane adhesive is that the liquid electrolyte is a liquid substance and is difficult to solidify. After the two-component polyurethane adhesive is completely solidified, the uncured liquid electrolyte or ionic liquid will remain in the curing system to form a "plasticizer", which changes the internal structure of the curing system. The presence of this "plasticizer" has a greater negative impact on the bonding strength and will greatly reduce the bonding performance of the two-component polyurethane adhesive. In addition, due to the poor compatibility between inorganic solid electrolyte materials and organic polyurethane adhesives, it is usually difficult to evenly disperse in the polyurethane adhesive system, which limits its application in electrically disassembled polyurethane adhesives.
[0009] The key to the present invention is to introduce a specific solid electrolyte (oxide-based solid electrolyte and / or sulfide-based solid electrolyte) into a two-component polyurethane adhesive in the presence of a silane coupling agent, and to obtain component A by combining a first solid electrolyte with a first polyol compound, a small molecule chain extender, a first silane coupling agent, and an optional first filler, a catalyst, and a first water absorbent, and to obtain component B by combining a second solid electrolyte with an isocyanate-terminated polyurethane prepolymer, a second silane coupling agent, and an optional second water absorbent and a second filler. The components play a good synergistic role with each other, thereby obtaining a two-component polyurethane adhesive with excellent bonding performance and electrical disassembly. The reason is speculated to be that: the oxide-based solid electrolyte and the sulfide-based solid electrolyte themselves have high ionic conductivity in the solid state, and can undergo Faraday electrochemical reaction under power-on conditions, weakening the bonding force at the adhesive bonding interface, thereby giving the two-component polyurethane adhesive detachable properties. In addition, the two specific electrolytes, the oxide-based solid electrolyte and the sulfide-based solid electrolyte, have good compatibility with the two-component polyurethane adhesive under the synergistic effect of the silane coupling agent and can be well dispersed in the two-component polyurethane adhesive system. At the same time, the oxide-based solid electrolyte and the sulfide-based solid electrolyte will not form a "plasticizer" after the two-component polyurethane adhesive is cured, causing its internal structure to change and affect the bonding strength. On the contrary, the oxide-based solid electrolyte and the sulfide-based solid electrolyte themselves can also serve as fillers to reinforce the colloid, thereby improving the bonding properties of the two-component polyurethane adhesive. In summary, the electrically disassembled two-component polyurethane adhesive provided by the present invention has excellent bonding properties and high bonding strength after curing. It is expected to meet the market demand for high-performance adhesives that can be disassembled on demand and has broad practical application prospects. DETAILED DESCRIPTION
[0010] The two-component polyurethane adhesive provided by the present invention comprises independently preserved component A and component B, wherein the weight ratio of component A to component B is (1-2):1, such as 1:1, 1.2:1, 1.5:1, 1.8:1, 2:1 or any value therebetween. Component A comprises a first polyol compound, a small molecule chain extender, a first solid electrolyte, a first silane coupling agent, and optionally a first filler, a catalyst and a first water absorbent. The weight ratio of the first polyol compound to the first solid electrolyte is 100:(5-37.5), such as 100:5, 100:10, 100:15, 100:20, 100:25, 100:30, 100:35, 100:37.5 or any value therebetween. The mass ratio of the first polyol compound to the first silane coupling agent is 100:(5-25), such as 100:5, 100:8, 100:10, 100:12, 100:15, 100:18, 100:20, 100:22, 100:25 or any value therebetween. The B component includes an isocyanate-terminated polyurethane prepolymer, a second solid electrolyte, a second silane coupling agent, and an optional second water absorbent and a second filler. The weight ratio of the isocyanate-terminated polyurethane prepolymer to the second solid electrolyte is 100:(5-45), such as 100:5, 100:7, 100:9, 100:15, 100:20, 100:30, 100:35, 100:40, 100:45 or any value therebetween. The mass ratio of the isocyanate-terminated polyurethane prepolymer to the second silane coupling agent is 100:(5-40), such as 100:5, 100:7, 100:9, 100:15, 100:20, 100:25, 100:30, 100:35, 100:40 or any value therebetween. The first solid electrolyte and the second solid electrolyte are each independently an oxide-based solid electrolyte and / or a sulfide-based solid electrolyte. Among them, the structural features of the oxide-based solid electrolyte are preferably selected from at least one of NASICON type, garnet type and perovskite type. The structural features of the sulfide-based solid electrolyte are preferably selected from at least one of amorphous, crystalline and glass-ceramic types.
[0011] In some specific embodiments, in component A, the content of the polyol compound is preferably 40 to 75 parts by weight, such as 40, 45, 50, 55, 60, 65, 70, 75 parts by weight or any value therebetween; the content of the small molecule chain extender is preferably 0.3 to 2.5 parts by weight, such as 0.3, 0.5, 0.8, 1, 1.5, 2, 2.5 parts by weight or any value therebetween; the content of the first solid electrolyte is preferably 5 to 15 parts by weight, such as 5, 8, 10, 12, 15 parts by weight or any value therebetween; the content of the first silane coupling agent is preferably 5 to 10 parts by weight, such as 5, 6, 7, 8, 9, 10 parts by weight or any value therebetween; the content of the first filler is preferably 0 to 40 parts by weight, such as 0, 5, 10, 15, 20, 25, 30, 35, 40 parts by weight or any value therebetween; the content of the catalyst is preferably 0 to 3 parts by weight, such as 0, 0.1, 0.5, 1, 1.5, 2, 2.5, 3 parts by weight or any value therebetween; the content of the first water absorbent is preferably 0 to 3 parts by weight, such as 0, 0.1, 0.5, 1, 1.5, 2, 2.5, 3 parts by weight or any value therebetween.
[0012] In some specific embodiments, in component B, the content of the isocyanate-terminated polyurethane prepolymer is preferably 25 to 55 parts by weight, such as 25, 30, 35, 40, 45, 50, 55 parts by weight or any value therebetween; the content of the second solid electrolyte is preferably 5 to 15 parts by weight, such as 5, 8, 10, 12, 15 parts by weight or any value therebetween; the content of the second silane coupling agent is preferably 5 to 10 parts by weight, such as 5, 6, 7, 8, 9, 10 parts by weight or any value therebetween; the content of the second water absorbent is preferably 0.1 to 3 parts by weight, such as 0.1, 0.5, 1, 1.5, 2, 2.5, 3 parts by weight or any value therebetween; the content of the second filler is preferably 4 to 35 parts by weight, such as 4, 6, 8, 10, 15, 20, 25, 30, 35 parts by weight or any value therebetween.
[0013] In the present invention, the solid electrolyte is an oxide-based solid electrolyte and / or a sulfide-based solid electrolyte. The ionic conductivity of the oxide-based solid electrolyte and / or the sulfide-based solid electrolyte at room temperature is generally 10 -4S / cm or more, and its source and type can be various existing options. The D50 or D90 particle size of the solid electrolyte is preferably 0.3 to 30 μm, such as 0.3 μm, 0.5 μm, 0.8 μm, 1 μm, 5 μm, 10 μm, 20 μm, 30 μm or any value therebetween. When the D50 or D90 particle size of the solid electrolyte is within the above preferred range, it is more conducive to the uniform dispersion of the solid electrolyte in the two-component polyurethane adhesive system, giving it good electrical disassembly performance, and it is also more conducive to the reinforcing effect of the solid electrolyte as a filler, and cooperates with other raw material components to improve the bonding performance of the two-component polyurethane adhesive system. The term "D50 or D90" refers to the particle size corresponding to when the cumulative particle size distribution percentage of a sample reaches 50% or 90%.
[0014] In some specific embodiments, the functionality of the first polyol compound is preferably 2 to 4, such as 2, 3, 4 or any value therebetween. The number average molecular weight (Mn) of the first polyol compound is preferably 200 to 3000 g / mol, such as 200 g / mol, 500 g / mol, 800 g / mol, 1000 g / mol, 1500 g / mol, 2000 g / mol, 2500 g / mol, 3000 g / mol or any value therebetween. The first polyol is preferably selected from at least one of polyether polyols, polyester polyols, castor oil derivative polyols, polyether-modified castor oil, hydroxyl-terminated polybutadiene polyols, polycarbonate polyols and polyacrylate polyols.
[0015] In some specific embodiments, the content of isocyanate groups in the isocyanate-terminated polyurethane prepolymer is preferably 10 to 25wt%, such as 10wt%, 12wt%, 15wt%, 18wt%, 20wt%, 25wt% or any value therebetween. The isocyanate-terminated polyurethane prepolymer can be commercially available, and can be a prepolymer obtained by reacting a second polyol compound with a polyisocyanate compound, and the reaction conditions can be conventionally selected in the art. The second polyol compound is preferably selected from at least one of polyether polyols, polyester polyols, castor oil polyols, polyether-modified castor oil, hydroxyl-terminated polybutadiene polyols, polycarbonate polyols and polyacrylate polyols. The polyisocyanate compound is preferably selected from at least one of isophorone diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, diphenylmethane-4,4'-diisocyanate (MDI), hydrogenated MDI, polymeric MDI, 1,5-naphthalene diisocyanate, norbornane diisocyanate, o-toluene diisocyanate, xylylene diisocyanate (XDI), hydrogenated XDI, lysine diisocyanate, triphenylmethane triisocyanate, tris(isocyanate phenyl)thiophosphate, tetramethylxylylene diisocyanate and 1,6,10-undecane triisocyanate.
[0016] In some specific embodiments, the small molecule chain extender is preferably a diol compound, and specific examples thereof include but are not limited to: ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,2-propylene glycol, 1,3-butanediol, 2,3-butanediol, 2-methyl-1,3-propylene glycol, 1,2-pentanediol, 2,4-pentanediol, 2-methyl-1,4-butanediol, 2,2- At least one of dimethyl-1,3-propanediol, 1,2-hexanediol, 1,3-hexanediol, 1,4-hexanediol, 2-methyl-1,5-pentanediol, 3-methyl-1,5-pentanediol, 2-ethyl-1,4-butanediol, 1,2-octanediol, 3,6-octanediol, 2-ethyl-1,3-hexanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-butyl-2-ethyl-1,3-propanediol, 2,7-dimethyl-3,6-octanediol, diethylene glycol, triethylene glycol, dipropylene glycol and tripropylene glycol.
[0017] In some specific embodiments, the first silane coupling agent and the second silane coupling agent are each independently selected from at least one of mercaptosilane, epoxysilane, aminosilane, alkenylsilane and isocyanatesilane, and specific examples thereof include but are not limited to: 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropylmethyldiethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3- At least one of glycidoxypropylmethyldiethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-(2-aminoethyl)aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropylmethyldimethoxysilane, 3-(methyl)acryloxypropyltrimethoxysilane, 3-(methyl)acryloxypropyltriethoxysilane, 3-(methyl)acryloxypropylmethyldimethoxysilane, 3-(methyl)acryloxypropylmethyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane and 3-isocyanatepropyltrimethoxysilane. The addition of the silane coupling agent helps to promote the uniform dispersion of the solid electrolyte in the two-component polyurethane hot melt adhesive system, thereby facilitating the electrical disassembly performance of the two-component polyurethane hot melt adhesive system.
[0018] In some specific embodiments, the first filler and the second filler are each independently selected from at least one of calcium carbonate, talc, kaolin, clay, quartz, montmorillonite, organic bentonite, hydrogenated castor oil, barium sulfate, fly ash, carbon black, fumed silica, aluminum hydroxide, magnesium hydroxide, aluminum oxide, antimony oxide, zinc borate, boron nitride, silicon carbide and melamine and its derivatives.
[0019] In some specific embodiments, the catalyst is preferably at least one selected from dibutyltin dilaurate, stannous octoate, triethylamine, diethylenetriamine, triethylenediamine, N-ethylmorpholine and 2,2-dimorpholinyl diethyl ether.
[0020] In some specific embodiments, the first water absorbing agent and the second water absorbing agent are each independently selected from at least one of a molecular sieve desiccant, an oxazolidine dehydrating agent, p-toluenesulfonyl isocyanate and triethyl orthoformate.
[0021] The preparation method of the two-component polyurethane adhesive provided by the present invention comprises: mixing a first polyol compound, a small molecule chain extender, a first solid electrolyte, a first silane coupling agent, and an optional first filler, a catalyst, and a first water absorbent to obtain a component A; mixing an isocyanate-terminated polyurethane prepolymer, a second solid electrolyte, a second silane coupling agent, and an optional second water absorbent and a second filler to obtain a component B; and the components A and B are stored independently.
[0022] In the preparation process of the above two-component polyurethane adhesive, the mixing and adding order of the raw material components can be arbitrarily combined, and the specific implementation method is preferably:
[0023] For component A: S1, stirring the first polyol compound, the small molecule chain extender, the first silane coupling agent, and the optional first water absorbent and the catalyst at 100-120° C. and vacuum conditions at a speed of 100-200 r / min for 1-3 hours to obtain a premix, and transferring the premix to a mixing tank; S2, adding the first solid electrolyte and the optional first filler to the premix, placing the mixing tank in a homogenizer, mixing at a speed of 1500-3000 r / min for 10-20 minutes, and scraping the filler on the wall of the mixing tank into the raw materials with a scraper during mixing to obtain component A;
[0024] For component B: S3, add the isocyanate-terminated polyurethane prepolymer, the second silane coupling agent and the optional second water absorbent into a mixing tank, and mix them in a homogenizer at a speed of 1500-3000 r / min for 5-10 min to obtain a premix; S4, add the second solid electrolyte and the optional second filler into the premix, and mix them in a homogenizer at a speed of 1500-3000 r / min for 10-20 min. During the mixing, the filler on the wall of the mixing tank can be scraped into the raw material with a scraper to obtain component B;
[0025] Transfer components A and B into a two-component mixing hose and vacuum seal them for storage.
[0026] The application of the two-component polyurethane adhesive provided by the present invention in products with adhesive disassembly requirements. Specifically, the adhesive disassembly conditions include: the voltage is preferably 1 to 100V, such as 1V, 3V, 5V, 8V, 10V, 20V, 50V, 60V, 80V, 100V or any value therebetween, and the power-on time is preferably 1s to 60min, 1s, 2s, 15s, 30s, 50s, 1min, 2min, 5min, 10min, 20min, 30min, 40min, 50min, 60min or any value therebetween. In addition, the bonding substrate used by the two-component polyurethane adhesive is a conductive substrate.
[0027] The present invention will be described in detail below through specific embodiments.
[0028] The parts involved in the following examples and comparative examples are all parts by weight.
[0029] The raw materials and sources in the following examples and comparative examples are as follows:
[0030] Castor oil polyol polycin GR-340, purchased from Vertellus, Mn = 370 mol / L, functionality 2.9; poly(ethylene glycol phthalate) diol, purchased from Stepan, brand PS-70L, Mn = 1600 mol / L, functionality 2; castor oil polyol polycin GR-160, purchased from Vertellus, Mn = 928 mol / L, functionality 2.7; polyoxypropylene ether diol, purchased from Dow Chemical Company, brand name Voranol-2120, Mn = 2000 mol / L, functionality 2; polyether polyol N303, purchased from Jiangsu Zhongshan Chemical Co., Ltd., Mn = 300 g / mol, functionality 3; polyhexane phthalate diol, purchased from Stepan, brand name PH-56, Mn = 2000 g / mol, functionality 2; castor oil polyol polycin GR-220, purchased from Vertellus, Mn = 650 mol / L, functionality is 2.8; poly neopentyl adipate diol, purchased from Qingdao Xinyutian Chemical Co., Ltd., brand name POL-737, Mn = 3000 g / mol, functionality is 2; poly diethylene phthalate diol, purchased from Stepan, brand name PD-56, Mn = 2000 mol / L, functionality is 2.
[0031] Sulfide-based solid electrolyte FL-LPSC, D90 = 20 μm, purchased from Zhejiang Fengli New Energy Technology Co., Ltd., brand LPSC-20000, ionic conductivity at room temperature is 6*10 -3 S / cm; garnet-type oxide-based solid electrolyte FL-GTEP, D50 = 0.5 μm, purchased from Zhejiang Fengli New Energy Technology Co., Ltd., brand GTEP-500, ionic conductivity ≥ 8*10 at room temperature -4 S / cm; NASICON oxide-based solid electrolyte LATP, D50 = 0.3 μm, purchased from Zhejiang Fengli New Energy Technology Co., Ltd., brand LATP-300, ionic conductivity at room temperature ≥ 6*10 -4 S / cm; sulfide-based solid electrolyte FL-LPSC, D50 = 30 μm, purchased from Zhejiang Fengli New Energy Technology Co., Ltd., brand LPSC-30000, ionic conductivity at room temperature is 1*10 -2S / cm; NASICON type oxide-based solid electrolyte LATP, D50 = 0.6 μm, purchased from Zhejiang Fengli New Energy Technology Co., Ltd., brand LATP-600, ionic conductivity ≥ 6*10 at room temperature -4 S / cm; NASICON oxide-based solid electrolyte LATP, D50 = 0.1 μm, purchased from Bluegoo New Energy Technology Co., Ltd., brand LG1117, ionic conductivity at room temperature is 5*10 -4 S / cm~1*10 -3 S / cm; sulfide-based solid electrolyte LGPS, D50 = 50 μm, purchased from Shenzhen ASML New Energy Co., Ltd., brand LGPS-50 μm, ionic conductivity at room temperature is ≥7*10 -3 S / cm; Polyethylene oxide PEO solid electrolyte, purchased from Cluder, brand E-30, ionic conductivity at room temperature is 6.29*10 -6 S / cm.
[0032] The p-toluenesulfonyl isocyanate water absorbent was purchased from Borchers, Germany, with the brand name Additive TI; the triethyl orthoformate water absorbent was purchased from Borchers, Germany, with the brand name Additive OF; the adsorbent molecular sieve water absorbent was purchased from Arkema, with the brand name Siliporite SA1702.
[0033] Example 1
[0034] Component A: 16.57 parts of castor oil polyol polycin GR-340, 26.94 parts of poly(ethylene phthalate) glycol PS-70L, 0.76 parts of butanediol, 7.00 parts of 3-mercaptopropyltrimethoxysilane, 1.50 parts of water absorbent Additive OF, and 0.50 parts of dibutyltin dilaurate were added to a reaction bottle, stirred at a speed of 150 r / min for 2 hours under vacuum conditions to obtain a premix, and the premix was transferred to a mixing tank; 37.73 parts of calcium carbonate and 9.00 parts of sulfide-based solid electrolyte FL-LPSC (D90=20 μm) were added to the premix, the mixing tank was placed in a homogenizer, mixed at a speed of 2000 r / min for 8 minutes, and then the raw materials on the wall of the mixing tank were scraped into the system with a scraper, and the mixing was continued at a speed of 2000 r / min for 8 minutes to obtain component A;
[0035] Component B: 14.14 parts of isocyanate-terminated polyurethane prepolymer Suprasec2444, 40.59 parts of isocyanate-terminated polyurethane prepolymer Desmodur E22, 5.00 parts of vinyl trimethoxy silane, and 2.50 parts of dewatering agent Siliporite SA1702 were added to a mixing tank, and mixed at a speed of 2000 r / min for 8 minutes in a homogenizer to obtain a premix; 30.77 parts of aluminum hydroxide and 6.00 parts of sulfide-based solid electrolyte FL-LPSC (D90 = 20 μm) were added to the above premix, and mixed at a speed of 2000 r / min for 8 minutes in a homogenizer; then the raw materials on the wall of the mixing tank were scraped into the system with a scraper, and the mixture was mixed at a speed of 2000 r / min for 8 minutes to obtain component B;
[0036] Then, components A and B are transferred to a two-component mixing hose to obtain a two-component polyurethane adhesive, which is then vacuum-sealed and stored for later use. When used, the components A and B are mixed in a weight ratio of 1:1.
[0037] Example 2
[0038] Component A: 17.65 parts of castor oil polyol polycin GR-160, 50.44 parts of polyoxypropylene ether glycol Voranol-2120, 1.49 parts of hexanediol, 8.00 parts of 3-aminopropyl trimethoxysilane, 1.50 parts of water absorbent Additive TI, and 2.00 parts of stannous octoate were added to a reaction bottle, stirred at a speed of 150 r / min for 2 hours under vacuum conditions to obtain a premix, and the premix was transferred to a mixing tank; 5.92 parts of aluminum oxide and 13.00 parts of garnet-type oxide-based solid electrolyte FL-GTEP (D50=0.5 μm) were added to the above premix, the mixing tank was placed in a homogenizer, mixed at a speed of 2000 r / min for 8 minutes, and then the raw materials on the wall of the mixing tank were scraped into the system with a scraper, and the mixing was continued at a speed of 2000 r / min for 8 minutes to obtain component A;
[0039] Component B: 9.23 parts of isocyanate-terminated polyurethane prepolymer Suprasec2021, 21.19 parts of isocyanate-terminated polyurethane prepolymer Desmodur XP2762, 6.00 parts of 3-glycidoxypropyltrimethoxysilane, and 1.00 parts of water absorbent Additive TI were added to a mixing tank, and mixed at a speed of 2000 r / min for 8 minutes in a homogenizer to obtain a premix; 26.58 parts of aluminum hydroxide and 6.00 parts of garnet-type oxide-based solid electrolyte FL-GTEP (D50=0.5 μm) were added to the above premix, and mixed at a speed of 2000 r / min for 8 minutes in a homogenizer; then the raw materials on the wall of the mixing tank were scraped into the system with a scraper, and the mixture was continued to be mixed at a speed of 2000 r / min for 8 minutes to obtain component B;
[0040] Then, components A and B are transferred to a two-component mixing hose to obtain a two-component polyurethane adhesive, which is then vacuum-sealed and stored for later use. When used, the components A and B are mixed in a weight ratio of 1.43:1.
[0041] Example 3
[0042] Component A: 9.16 parts of polyether polyol N303, 45.82 parts of poly(hexane phthalate) glycol ester diol PH-56, 1.68 parts of 2-ethyl-1,3-hexanediol, 5.00 parts of 3-mercaptopropyltrimethoxysilane, 1.50 parts of water absorbent Additive OF, and 2.00 parts of 2,2-dimorpholinyl diethyl ether were added to a reaction bottle, stirred at a speed of 150 r / min for 2 hours under vacuum conditions to obtain a premix, and the premix was transferred to a mixing tank; 27.84 parts of calcium carbonate and 7.00 parts of NASICON oxide-based solid electrolyte LATP (D50 = 0.3 μm) were added to the above premix, the mixing tank was placed in a homogenizer, mixed at a speed of 2000 r / min for 8 minutes, and then the raw materials on the wall of the mixing tank were scraped into the system with a scraper, and the mixing was continued at a speed of 2000 r / min for 8 minutes to obtain component A;
[0043] Component B: 19.24 parts of isocyanate-terminated polyurethane prepolymer Desmodur E23, 24.10 parts of isocyanate-terminated polyurethane prepolymer Desmodur E21, 10.00 parts of 3-isocyanatepropyltrimethoxysilane, and 1.50 parts of water absorbent Additive OF were added to a mixing tank, and mixed at a speed of 2000 r / min for 8 minutes in a homogenizer to obtain a premix; 27.84 parts of aluminum oxide and 12.00 parts of NASICON-type oxide-based solid electrolyte LATP (D50=0.3 μm) were added to the above premix, and mixed at a speed of 2000 r / min for 8 minutes in a homogenizer; then the raw materials on the wall of the mixing tank were scraped into the system with a scraper, and the mixture was continued to be mixed at a speed of 2000 r / min for 8 minutes to obtain component B;
[0044] Then, components A and B are transferred to a two-component mixing hose to obtain a two-component polyurethane adhesive, which is then vacuum-sealed and stored for later use. When used, the components A and B are mixed in a weight ratio of 1.25:1.
[0045] Example 4
[0046] Component A: 28.10 parts of castor oil polyol polycin GR-220, 41.33 parts of polyadipate neopentyl glycol ester diol POL-737, 0.37 parts of butanediol, 10.00 parts of 3-glycidoxypropyl trimethoxysilane, 0.50 parts of water absorbent Additive TI, and 1.50 parts of dibutyltin dilaurate were added to a reaction bottle, stirred at a speed of 150 r / min for 2 hours under vacuum conditions to obtain a premix, and the premix was transferred to a mixing tank; 7.20 parts of aluminum hydroxide and 11.00 parts of sulfide-based solid electrolyte FL-LPSC (D50 = 30 μm) were added to the above premix, the mixing tank was placed in a homogenizer, mixed at a speed of 2000 r / min for 8 minutes, and then the raw materials on the wall of the mixing tank were scraped into the system with a scraper, and continued to mix at a speed of 2000 r / min for 8 minutes to obtain component A;
[0047] Component B: 10.03 parts of isocyanate-terminated polyurethane prepolymer Desmodur E23, 20.17 parts of isocyanate-terminated polyurethane prepolymer Suprasec2021, 5.00 parts of 3-glycidoxypropylmethyldimethoxysilane, and 3.00 parts of water absorbent Additive TI were added to a mixing tank, and mixed at a speed of 2000 r / min for 8 minutes in a homogenizer to obtain a premix; 4.80 parts of aluminum hydroxide and 7.00 parts of sulfide-based solid electrolyte FL-LPSC (D50=30 μm) were added to the above premix, and mixed at a speed of 2000 r / min for 8 minutes in a homogenizer; then the raw materials on the wall of the mixing tank were scraped into the system with a scraper, and the mixture was continued to be mixed at a speed of 2000 r / min for 8 minutes to obtain component B;
[0048] Then, components A and B are transferred to a two-component mixing hose to obtain a two-component polyurethane adhesive, which is then vacuum-sealed and stored for later use. When used, the components A and B are mixed in a weight ratio of 2:1.
[0049] Example 5
[0050] Component A: 5.35 parts of castor oil polyol polycin GR-340, 65.30 parts of poly(ethylene phthalate) glycol ester diol PD-56, 1.93 parts of hexanediol, 5.00 parts of 3-glycidoxypropyl trimethoxysilane, 0.10 parts of water absorbent Siliporite SA1702, and 3.00 parts of stannous octoate were added to a reaction bottle, stirred at a speed of 150 r / min for 2 hours under vacuum conditions to obtain a premix, and the premix was transferred to a mixing tank; 13.32 parts of calcium carbonate and 6.00 parts of NASICON oxide-based solid electrolyte LATP (D50=0.6 μm) were added to the above premix, the mixing tank was placed in a homogenizer, mixed at a speed of 2000 r / min for 8 minutes, and then the raw materials on the wall of the mixing tank were scraped into the system with a scraper, and the mixing was continued at a speed of 2000 r / min for 8 minutes to obtain component A;
[0051] Component B: 9.14 parts of isocyanate-terminated polyurethane prepolymer Desmodur E23, 18.28 parts of isocyanate-terminated polyurethane prepolymer Desmodur XP2762, 8.00 parts of 3-isocyanatepropyltrimethoxysilane, and 2.00 parts of water absorbent Siliporite SA1702 were added to a mixing tank, and mixed at a speed of 2000 r / min for 8 minutes in a homogenizer to obtain a premix; 14.58 parts of aluminum oxide and 8.00 parts of NASICON-type oxide-based solid electrolyte LATP (D50=0.6 μm) were added to the above premix, and mixed at a speed of 2000 r / min for 8 minutes in a homogenizer; then the raw materials on the wall of the mixing tank were scraped into the system with a scraper, and the mixture was continued to be mixed at a speed of 2000 r / min for 8 minutes to obtain component B;
[0052] Then, components A and B are transferred to a two-component mixing hose to obtain a two-component polyurethane adhesive, which is vacuum-sealed and stored for later use. When used, the components A and B are mixed in a weight ratio of 1.67:1.
[0053] Example 6
[0054] The polyurethane hot melt adhesive was prepared according to the method of Example 1, except that the same amount of oxide-based solid electrolyte LATP with D50=0.1 μm was used in both component A and component B instead of sulfide-based solid electrolyte FL-LPSC with D90=20 μm, and the other conditions were the same as those of Example 1, thereby preparing a two-component polyurethane adhesive. When used, the components A and B were mixed in a weight ratio of 1:1.
[0055] Example 7
[0056] The polyurethane hot melt adhesive was prepared according to the method of Example 1, except that the same number of sulfide-based solid electrolyte LGPS-50μm with D50=50μm was used in both component A and component B instead of sulfide-based solid electrolyte FL-LPSC with D90=20μm, and the other conditions were the same as those in Example 1, thereby preparing a two-component polyurethane adhesive. When used, the components A and B were mixed in a weight ratio of 1:1.
[0057] Comparative Example 1
[0058] The polyurethane hot melt adhesive was prepared according to the method of Example 1, except that the same amount of polyethylene oxide PEO solid electrolyte (Croode Company, brand E-30, ionic conductivity of 6.29*10 at room temperature) was used in both component A and component B. - 6S / cm) was used to replace the sulfide-based solid electrolyte FL-LPSC with D90=20 μm, and the other conditions were the same as those in Example 1, thereby preparing a two-component polyurethane adhesive. When used, the A component and the B component were mixed in a weight ratio of 1:1.
[0059] Comparative Example 2
[0060] A reference two-component polyurethane adhesive was prepared according to the method of Example 1, except that no sulfide-based solid electrolyte FL-LPSC was added to component A and component B, and the other conditions were the same as those of Example 1, thereby preparing a reference two-component polyurethane adhesive. When used, component A and component B were mixed in a weight ratio of 1:1.
[0061] Comparative Example 3
[0062] A reference two-component polyurethane adhesive was prepared according to the method of Example 1, except that the addition amount of 3-mercaptopropyltrimethoxysilane and sulfide-based solid electrolyte FL-LPSC in component A was reduced to 1 part, and the addition amount of vinyltrimethoxysilane and sulfide-based solid electrolyte FL-LPSC in component B was reduced to 1 part, and the other conditions were the same as in Example 1, thereby preparing a reference two-component polyurethane adhesive. When used, component A and component B were mixed in a weight ratio of 1:1.
[0063] Comparative Example 4
[0064] Component A: 27.91 parts of castor oil polyol polycin GR-160, 39.86 parts of polyoxypropylene ether glycol Voranol-2120, 0.90 parts of butanediol, 1.00 parts of 3-aminopropyl trimethoxysilane, 1.5 parts of water absorbent Additive OF, 0.50 parts of stannous octoate, 5.00 parts of lithium trifluoromethanesulfonate, and 15.00 parts of propylene carbonate were added to a reaction bottle, stirred at a speed of 150 r / min for 2 hours under vacuum conditions to obtain a premix, and the premix was transferred to a mixing tank; 8.33 parts of calcium carbonate were added to the above premix, the mixing tank was placed in a homogenizer, mixed at a speed of 2000 r / min for 8 minutes, and then the raw materials on the wall of the mixing tank were scraped into the system with a scraper, and continued to mix at a speed of 2000 r / min for 8 minutes to obtain component A;
[0065] Component B: 16.74 parts of isocyanate-terminated polyurethane prepolymer Desmodur XP2762, 14.59 parts of isocyanate-terminated polyurethane prepolymer Suprasec2021, 1.00 parts of 3-isocyanatepropyltrimethoxysilane, and 2.50 parts of water absorbent Additive OF were added to a mixing tank, and mixed in a homogenizer at a speed of 2000 r / min for 8 minutes to obtain a premix; 15.17 parts of aluminum oxide were added to the above premix, and mixed in a homogenizer at a speed of 2000 r / min for 8 minutes; then the raw materials on the wall of the mixing tank were scraped into the system with a scraper, and the mixture was continued to be mixed at a speed of 2000 r / min for 8 minutes to obtain component B;
[0066] Then, components A and B are transferred to a two-component mixing hose to obtain a reference two-component polyurethane adhesive containing liquid electrolyte, which is then vacuum-sealed and stored for later use. When used, the components A and B are mixed in a weight ratio of 2:1.
[0067] Comparative Example 5
[0068] A reference two-component polyurethane adhesive was prepared according to the method of Example 1, except that 3-mercaptopropyltrimethoxysilane was not added to component A, and vinyltrimethoxysilane was not added to component B. The other conditions were the same as those of Example 1, thereby preparing a reference two-component polyurethane adhesive. When used, component A and component B were mixed in a weight ratio of 1:1.
[0069] Test Case
[0070] The two-component polyurethane adhesives prepared in the above examples and comparative examples were tested for bonding strength, heat resistance, and high temperature and high humidity resistance before and after power-on according to the following method. The results are shown in Table 1.
[0071] (1) Bonding strength test before power-on: At room temperature, a two-component polyurethane adhesive obtained by mixing component A and component B in the embodiment and comparative example in a certain proportion was applied on a stainless steel substrate using a dispensing machine to form a rectangular adhesive line of 25 mm*4 mm, and then another stainless steel substrate was bonded to the stainless steel substrate. After bonding, the sample was cured in an environment of 25°C and 50% RH for 7 days, and then the prepared bonding sample was run in the shear direction at a speed of 10 mm / min using a universal material testing machine until the sample failed to bond, and the maximum force value displayed by the instrument was recorded. The shear bonding strength of the adhesive to the stainless steel substrate after curing for another 7 days was calculated based on the bonding area.
[0072] (2) Bond strength test after power-on: Dispense the glue according to the method in (1), and after curing for 7 days, obtain the sample to be tested. Clamp the positive and negative wires of the DC power supply at both ends of the sample, respectively. Power is applied at 48 V for 30 min or at 60 V for 20 min. After the power-on is completed, remove the sample and use a universal material testing machine to run the prepared bonding sample along the shear direction at a speed of 10 mm / min until the sample fails. Record the maximum force value displayed by the instrument and calculate the shear bonding strength of the adhesive to the stainless steel substrate after power-on based on the bonding area (when the bonding strength is below 2 MPa, it is removable).
[0073] (3) Heat resistance (80°C) test: The test sample was obtained after dispensing and curing for 7 days according to the method in (1). The test sample was placed in an oven at 80°C for 20 min. The prepared bonding sample was then run in an 80°C environment at a speed of 10 mm / min along the shear direction using a universal material testing machine until the bonding of the sample failed. The maximum force value displayed by the instrument was recorded, and the shear bonding strength of the adhesive to the stainless steel substrate in a high temperature environment of 80°C was calculated based on the bonding area.
[0074] (4) High temperature and high humidity resistance test: The test sample was obtained after dispensing and curing for 7 days according to the method in (1). The test sample was placed in a high temperature and high humidity oven at 85°C and 85% RH for 7 days. The prepared bonding sample was run along the shear direction at a speed of 10 mm / min using a universal material testing machine until the bonding of the sample failed. The maximum force value displayed by the instrument was recorded, and the shear bonding strength of the adhesive to the stainless steel substrate after high temperature and high humidity aging was calculated based on the bonding area.
[0075] Table 1
[0076]
[0077]
[0078] It can be seen from the results of Examples 1 to 7 that the two-component polyurethane adhesive provided by the present invention has excellent bonding strength after curing, and the bonding strength is reduced to below 2MPa after power-on. It is detachable and has good heat resistance and high temperature and high humidity resistance. From the results of Example 1 and Comparative Example 1, it can be seen that when a polymer solid electrolyte is added, the bonding strength of the two-component polyurethane adhesive is reduced, and the heat resistance and high temperature and high humidity resistance are poor. After power-on, the bonding strength is greater than 2MPa, and it is not detachable. From the results of Example 1 and Comparative Examples 2 and 3, it can be seen that when no oxide-based or sulfide-based solid electrolyte is added, or when the amount of silane coupling agent and solid electrolyte added is too small, the bonding strength, heat resistance, and high temperature and high humidity resistance of the two-component polyurethane adhesive decrease, and the bonding strength is greater than 2MPa after power-on, and it is not detachable. From the results of Example 1 and Comparative Example 5, it can be seen that when no silane coupling agent is added, the bonding strength, heat resistance and high humidity and high temperature resistance of the two-component polyurethane hot melt adhesive are poor, and the bonding strength decreases slightly after power is turned on, and the bonding strength is greater than 2MPa, and it is not removable. From the results of Examples 1 to 7 and Comparative Example 4, it can be seen that compared with the traditional two-component polyurethane adhesive with electrical disassembly performance, the two-component polyurethane adhesive provided by the embodiment of the present invention has better bonding performance, heat resistance and high temperature and high humidity resistance.
[0079] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.
Claims
1. A two-component polyurethane adhesive, characterized in that: The two-component polyurethane adhesive comprises independently preserved component A and component B; the weight ratio of the component A to the component B is (1-2):1; the component A contains a first polyol compound, a small molecule chain extender, a first solid electrolyte, a first silane coupling agent, and optionally a first filler, a catalyst and a first water absorbent; the mass ratio of the first polyol compound, the first solid electrolyte and the first silane coupling agent is 100:(5-37.5):(5-25); the component B contains an isocyanate-terminated polyurethane prepolymer, a second solid electrolyte, a second silane coupling agent, and optionally a second water absorbent and a second filler; the mass ratio of the isocyanate-terminated polyurethane prepolymer, the second solid electrolyte and the second silane coupling agent is 100:(5-45):(5-40); the first solid electrolyte and the second solid electrolyte are each independently an oxide-based solid electrolyte and / or a sulfide-based solid electrolyte.
2. The two-component polyurethane adhesive according to claim 1, characterized in that: In component A, the content of the polyol compound is 40 to 75 parts by weight, the content of the small molecule chain extender is 0.3 to 2.5 parts by weight, the content of the first solid electrolyte is 5 to 15 parts by weight, the content of the first silane coupling agent is 5 to 10 parts by weight, the content of the first filler is 0 to 40 parts by weight, the content of the catalyst is 0 to 3 parts by weight, and the content of the first water absorbent is 0 to 3 parts by weight.
3. The two-component polyurethane adhesive according to claim 1, characterized in that: In component B, the content of the isocyanate-terminated polyurethane prepolymer is 25 to 55 parts by weight, the content of the second solid electrolyte is 5 to 15 parts by weight, the content of the second silane coupling agent is 5 to 10 parts by weight, the content of the second water absorbent is 0 to 3 parts by weight, and the content of the second filler is 0 to 35 parts by weight.
4. The two-component polyurethane adhesive according to claim 1, characterized in that: The functionality of the first polyol compound is 2 to 4; optionally, the number average molecular weight of the first polyol compound is 200 to 3000 g / mol; optionally, the first polyol compound is selected from at least one of polyether polyol, polyester polyol, castor oil derivative polyol, polyether-modified castor oil, hydroxyl-terminated polybutadiene polyol, polycarbonate polyol and polyacrylate polyol.
5. The two-component polyurethane adhesive according to claim 1, characterized in that: The ionic conductivity of the first solid electrolyte and the second solid electrolyte at room temperature is 10 -4 S / cm or more; optionally, the D50 or D90 particle size of the first solid electrolyte and the second solid electrolyte are each independently 0.3 to 30 μm.
6. The two-component polyurethane adhesive according to claim 1, characterized in that: The content of isocyanate groups in the isocyanate-terminated polyurethane prepolymer is 10 to 25 wt %.
7. The two-component polyurethane adhesive according to claim 1, characterized in that: The first silane coupling agent and the second silane coupling agent are each independently selected from at least one of mercaptosilane, epoxysilane, aminosilane, alkenylsilane and isocyanatesilane.
8. The two-component polyurethane adhesive according to claim 1, characterized in that: The first filler and the second filler are each independently selected from at least one of calcium carbonate, talc, kaolin, clay, quartz, montmorillonite, organic bentonite, hydrogenated castor oil, barium sulfate, fly ash, carbon black, fumed silica, aluminum hydroxide, magnesium hydroxide, aluminum oxide, antimony oxide, zinc borate, boron nitride, silicon carbide and melamine and its derivatives.
9. The method for preparing the two-component polyurethane adhesive according to any one of claims 1 to 8, characterized in that: The method comprises: mixing a first polyol compound, a small molecule chain extender, a first solid electrolyte, a first silane coupling agent, and an optional first filler, a catalyst, and a first water absorbent to obtain a component A; mixing an isocyanate-terminated polyurethane prepolymer, a second solid electrolyte, a second silane coupling agent, and an optional second water absorbent and a second filler to obtain a component B; and the components A and B are stored independently.
10. Use of the two-component polyurethane adhesive according to any one of claims 1 to 8 in bonding electronic products.